2017
DOI: 10.24070/bjvp.1983-0246.v10i1p38-42
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and progesterone receptors immunolabeling in mammary solid carcinoma in an African Hedgehog (Atelerix albiventris) with concurrent uterine fibrosarcoma

Abstract: Fernandes, et al.; Estrogen and progesterone receptors immunolabeling in mammary solid carcinoma in an African Hedgehog (Atelerix albiventris) with concurrent uterine fibrosarcoma. Braz J Vet Pathol, 2017, 10(1), 38 -42. DOI: 10.24070/bjvp.1983 Brazilian AbstractThe African Hedgehog (Atelerix albiventris) has gained popularity as a pet in several parts of the world. This is a report of a concomitant finding of spontaneous mammary and uterine tumors in an adult female African Hedgehog. The animal presented ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Uterine polyps cause hematuria and vaginal bleeding, and were sometimes found as necrotic tissues protruding from the vulva. No unified diagnosis was possible because these lesions were diagnosed in previous reports using variable terms, such as endometrial polyp, adenoleiomyosarcoma, adenosarcoma, endometrial stromal cell sarcoma, adenoleiomyoma, uterine adenocarcinoma, carcinosarcoma, uterine fibrosarcoma, and uterine spindle cell tumor [ 4 , 5 , 8 , 11 , 16 , 19 ]. Previous studies had indicated that the prefix “adeno” with the name of a mesenchymal neoplasm indicates the presence of a non-neoplastic epithelial component within a mesenchymal neoplasm [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uterine polyps cause hematuria and vaginal bleeding, and were sometimes found as necrotic tissues protruding from the vulva. No unified diagnosis was possible because these lesions were diagnosed in previous reports using variable terms, such as endometrial polyp, adenoleiomyosarcoma, adenosarcoma, endometrial stromal cell sarcoma, adenoleiomyoma, uterine adenocarcinoma, carcinosarcoma, uterine fibrosarcoma, and uterine spindle cell tumor [ 4 , 5 , 8 , 11 , 16 , 19 ]. Previous studies had indicated that the prefix “adeno” with the name of a mesenchymal neoplasm indicates the presence of a non-neoplastic epithelial component within a mesenchymal neoplasm [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of the tissues in the oral mucosa were diagnosed as having non-neoplastic lesions. Tooth root abscesses have been reported [ 4 ] and these lesions are thought to be formed by tartar or bacterial infection.…”
Section: Discussionmentioning
confidence: 99%